A Framework for Building Change Detection using Remote Sensing Imagery (International Journal of Emerging Trends in Science and Technology, 2017)
Change detection of building from high-resolution remote sensing images is an important and challengingresearch field in remote sensing. In this paper a novel technique for building change detection from remotesensing imagery is presented. First, The Morphological Building Index (MBI) features values are computedfor each of the pair images from our datasets and then change of these two MBI images is measured toindicate the building change. For evaluation purpose, the experiments are carried on IKONOS and QuickBird images. The results show that the proposed technique can attain acceptable correctness rates above90% with overall errors fewer than 9%. Compared with state-of-the-art methods in building changedetection; the proposed framework is computationally much more efficient while achieving betterperformance in terms of correctness, completeness, and quality.